ANALISIS CULTURE SHOCK PADA PEGAWAI DI ERA NEW NORMAL - Sekar Kama Dianingrum; Onny Fitriana Sitorus (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
This study aims to determine the impact of culture shock on employees of the Ministry of Agriculture in the new normal era. This research uses descriptive qualitative research methods. The data using primary data is conducting interviews with employees of Kementerian Pertanian and secondary data using literature and documentation relevant to the problem taken. Data analysis is carried out through the stages of Data Reduction, Data Presentation and conclusion. The work from home system is allowed in a sector that focuses on services. Differences in work culture will cause the impact of culture shock which is characterized by a sense of anxiety and fear, to find out the result, researchers use ABC theory in culture shock. The results of this study show that the culture shock that comes from the interpersonal of employees who are dominated by Behavior component includes communication and coordination that has not been effective due to the implementation of 50% WFO and 50% WFH, services that have not been delivered optimally, fear of the spread of the virus from colleagues, and have not been able to adjust homework and offices for female employees. This is because employees are able to adjust to the new normal era.